The Role of Predicted Emotion Regulation in Posttraumatic Growth and Development of Blind Veterans - Aghil Hosseinlu; Masomeh Esmail'i (Vesnu Publications, 2018)
Introduction: For people, the difficulty in setting up emotions is a kind of incompatibility, and represents a high risk factor for mental health. The present study examined the predictive role of emotion regulation in the posttraumatic growth and development of blind veterans. Materials and Methods: In this descriptive-correlation study, participants were 110 blind veterans who were selected using convenience sampling method. Calhoun and Tedeschi emotion regulation difficulty questionnaire as well as Gratz and Roemer posttraumatic growth and development questionnaire were completed with the help of questioners. The data were analyzed using Pearson correlation and multiple linear regression tests via SPSS software. Results: There was a negative relationship between emotion regulation difficulty with posttraumatic growth and development. Moreover, as a result of regression analysis between emotion regulation difficulty with posttraumatic growth and development, F statistic value was 4.319, and the standardized regression coefficient was -0.196. Therefore emotion regulation was able to predict posttraumatic growth and development (P < 0.05). Conclusion: According to research findings, it seems that if emotional regulation is appropriately performed, it is not only possible to prevent high-risk behaviors, but also leads to individual's growth and development.